The Application Of Coconut Waste As Green Roof Materials For Stormwater Quality Improvement - Nazrul Aizad, M Taip (2023)
The urbanization increases impervious areas and diversifies urban land use practices in hydrology and the environment. Moreover, the amount of accumulated dirt on the rooftop can cause sedimentation and give bad quality stormwater. When stormwater flows across construction sites and unplanted fields such as rooftops, it picks up loose dirt, creating mud, which is quickly carried into streams where it causes sedimentation and clogs the waterways, lakes, and reservoirs, which can cause floods, kills fish and aquatic animals. Hence, impervious areas such as rooftops, driveways, roads, parking lots, and footpaths lessen the catchment permeability resulting the increases of peak flow runoff, giving bad quality of the stormwater quality and increase the heat temperature. The objectives of this study are to construct a green roof model that can improve the surface runoff quality using coconut waste as the green roof materials and evaluate the performance of green roofs in improving stormwater quality. The materials that was used for the green roof for this study is the Philippines Grass as the vegetation layer, burnt soil as the substrate layer, coconut fiber as the filter layer, burnt crush coconut shell as the drainage layer, and lastly the bitumen sealant for the waterproofing layer. The water quality parameters that were tested in this study is Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Suspended Solids (TSS). The result shows that the green roof recycled waste is not very effective compared to the other roof. From the graph, it showed that the concentration for the green roof recycled waste is the highest value in TSS and COD which is 40.3 mg/L and 410 mg/L, but it has a low concentration in BOD which is 23.7 mg/L. The caused might be because of the preparation of the green roof material is not done properly, which resulting the high concentration of stormwater in water quality parameter such as COD. To improve the green roof system, the concentration can be reduced by change the material of the drainage layer with the raw coconut shell. As conclusion, the green roof model that can improve the surface runoff quality using coconut waste as the green roof materials has been constructed but the green roof is not capable to improve the quality of the concentration of pollutants in stormwater.